2016
DOI: 10.1073/pnas.1518527113
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated beating of algal flagella is mediated by basal coupling

Abstract: Cilia and flagella often exhibit synchronized behavior; this includes phase locking, as seen in Chlamydomonas, and metachronal wave formation in the respiratory cilia of higher organisms. Since the observations by Gray and Rothschild of phase synchrony of nearby swimming spermatozoa, it has been a working hypothesis that synchrony arises from hydrodynamic interactions between beating filaments. Recent work on the dynamics of physically separated pairs of flagella isolated from the multicellular alga Volvox has… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
199
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(206 citation statements)
references
References 79 publications
7
199
0
Order By: Relevance
“…The study by Quaranta, Aubin-Tam & Tam (2015) showed no evidence of synchrony in these mutants. A more extensive examination (Wan & Goldstein 2016) showed that when the flagella of these mutants are close enough together for strong hydrodynamic interactions then synchrony is observed, with the symmetries found in the measurements of separated Volvox somatic cells described above. Moreover, nature has provided us with not only biflagellates, but unicellular quadri-, octo-and even hexadecaflagellates, all with known and often elaborate networks of filamentary In each panel, the coloured bars depict time series of beat phases.…”
Section: R E Goldsteinsupporting
confidence: 55%
See 2 more Smart Citations
“…The study by Quaranta, Aubin-Tam & Tam (2015) showed no evidence of synchrony in these mutants. A more extensive examination (Wan & Goldstein 2016) showed that when the flagella of these mutants are close enough together for strong hydrodynamic interactions then synchrony is observed, with the symmetries found in the measurements of separated Volvox somatic cells described above. Moreover, nature has provided us with not only biflagellates, but unicellular quadri-, octo-and even hexadecaflagellates, all with known and often elaborate networks of filamentary In each panel, the coloured bars depict time series of beat phases.…”
Section: R E Goldsteinsupporting
confidence: 55%
“…Moreover, nature has provided us with not only biflagellates, but unicellular quadri-, octo-and even hexadecaflagellates, all with known and often elaborate networks of filamentary In each panel, the coloured bars depict time series of beat phases. Reproduced from Wan & Goldstein (2016).…”
Section: R E Goldsteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Which of the different mechanisms dominates in different biological systems will have to determined by future research. Open questions relate in particular to the role of elastic anchorage of the flagellar apparatus [37,73], and the waveform compliance of the flagellar beat [34]. It is not known, which features of the flagellar beat patterns determine whether in-phase or anti-phase synchronization will be stable, as observed e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This type of large scale coordinated beating pattern is of great importance for efficient propulsion [8][9][10][11][12]. It is now well established that hydrodynamic interactions play a crucial role [7,10,13,14] for the emergence of such large scale metachronal waves.…”
Section: Introductionmentioning
confidence: 98%